Uji Aktivitas Enzim Fibrinolitik Dari Makanan Fermentasi Kacang Koro (Mucuna Pruriens) Metode Clot Lysis In Vitro - Pamungkas, Bayu Aji; Indrayati, Ana; Pramukantoro, Ganet Eko (Jurnal Farmasi & Sains Indonesia, 2024)
Fibrinolytic enzymes are a group of serine proteases that can destroy blood clots (fibrin) in various thrombosis diseases. This study aims to determine the activity of fibrinolytic enzymes contained in jack bean tempeh using the in vitro clot lysis method. First, crude extraction of the jack bean tempeh enzyme was carried out by centrifugation to produce pellets and supernatants. Then purification using 70% ammonium sulfate salt, determination of enzyme protein levels using the Lowry method and fibrinolytic potential testing using the in vitro clot lysis method. The variations in extract concentrations used in the test were 12.5; 25; 50 and 100% with positive control Natokinase and negative control aquadest. This study showed the results of pellets after purification as much as 26.78 gr. Then it also showed an increase in protein level activity between before purification 22,515 µg / mL and after purification 27,215 µg / mL. In vitro clot lysis testing was carried out with several variations showing the most optimal variation in destroying blood clots was at 100% variation after purification with a lysis percentage of 61%. The most optimal results were also in the Two Way Anova test with a value of 63,592 samples after 100% concentration purification.